Co-inoculation of baculovirus and FMDV vaccine in mice, elicits very early protection against foot and mouth disease virus without interfering with long lasting immunity - Quattrocchi, Valeria; Molinari, Maria Paula; Langellotti, Cecilia Ana; Gnazzo, Victoria; Taboga, Oscar Alberto; Zamorano, Patricia Ines (Elsevier, 2019)
Baculoviruses (Bvs) potentiate the immune response against soluble antigens. We investigated whether Bv could be used as immunoactivator in foot-and-mouth disease (FMD) vaccines using the BALB/c mouse model. Mice were vaccinated with a single dose of inactivated FMDV (iFMDV), iFMDV + Bv, Bv, or culture medium. Humoral and cellular immune responses were higher in animals immunized with iFMDV + Bv than in mice vaccinated with iFMDV alone. Animals receiving iFMDV + Bv had significantly lower viremia at 2, 4 and 7 dpv, than those immunized with iFMDV alone. In order to prolong the immune response, iFMDV oil vaccine was co-inoculated with Bv. Animals receiving iFMDV oil vaccine + Bv were protected two days earlier than those receiving the iFMDV oil vaccine alone. Both formulations protected until 14 dpv, the last day of the experiment. This is the first report in which Bv is used as an adjuvant in a FMDV vaccine.